C1-C2 subluxation in enthesitis-related arthritis: two case reports and literature review of ten cases - Wing Hin Stanford Siu; Chao-Jan Wang; Chieh-Tsai Wu; Chao-Yi Wu; Liang-Shiou Ou (BMC, 2023)
Abstract Background C1-C2 subluxation is a rare complication of enthesitis-related arthritis (ERA). If left untreated, it may lead to functional impairment or cervical spinal cord compression. This study aims to highlight key points regarding the management of C1-C2 subluxation in ERA. Case presentation We present two cases of C1-C2 subluxation: an 8-year-old boy with ERA and 16-year-old boy with ERA with bilateral sacroiliitis. Ten cases of ERA in the literature were reviewed. The diagnosis of C1-C2 subluxation is mostly based on radiographs and cervical spine computed tomography. All patients were treated with non-steroidal anti-inflammatory drugs. Six ERA patients were treated surgically for cervical fusion. Most ERA patients with sacroiliitis had cervical collar protection. Neurologic abnormalities after treatment were not reported. Despite the use of cervical collar, cervical fusion and persisting ankylosis were found in two ERA patients with sacroiliitis without surgical treatment. Conclusions Cervical spine protection and ruling out spinal cord compression should be prioritized, in addition to controlling the underlying inflammation in ERA. Cervical halter traction may be applied after severe cervical inflammation is excluded. To reduce the risk of complications, early recognition and appropriate treatments of C1-C2 subluxation in ERA are essential.